2012
DOI: 10.1111/j.1365-2966.2011.20373.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Population III multiplicity on dark star formation

Abstract: We numerically study the mutual interaction between dark matter (DM) and Population III (Pop III) stellar systems in order to explore the possibility of Pop III dark stars within this physical scenario. We perform a cosmological simulation, initialized at z∼ 100, which follows the evolution of gas and DM. We analyse the formation of the first minihalo at z∼ 20 and the subsequent collapse of the gas to densities of 1012 cm−3. We then use this simulation to initialize a set of smaller scale ‘cut‐out’ simulations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…Numerical simulations of the collapse of rotating metal-free clouds indicate the appearance of a bar instability leading to the formation of two protostars in a binary (Saigo et al 2004). In recent simulations (Turk et al 2009;Stacy et al 2010;Greif et al 2011;Clark et al 2011;Stacy et al 2012), a similar result was shown. A massive protostellar cloud develops spiral structure, instabilities, and leads to the formation of several multiple systems.…”
Section: Population Of Stars -Modelssupporting
confidence: 79%
“…Numerical simulations of the collapse of rotating metal-free clouds indicate the appearance of a bar instability leading to the formation of two protostars in a binary (Saigo et al 2004). In recent simulations (Turk et al 2009;Stacy et al 2010;Greif et al 2011;Clark et al 2011;Stacy et al 2012), a similar result was shown. A massive protostellar cloud develops spiral structure, instabilities, and leads to the formation of several multiple systems.…”
Section: Population Of Stars -Modelssupporting
confidence: 79%
“…As our models do not include the effects of ionisation feedback from massive stars, we stopped our simulation at this point. However, we note that studies that have investigated the effect of this ionisation feedback find that it rapidly shuts off the supply of material to the disc, and hence will act to suppress fragmentation at later times (Stacy et al 2012;Hosokawa et al 2011).…”
Section: Secondary Fragmentationmentioning
confidence: 90%
“…This issue has been addressed recently by Stacy et al (2012), who performed a calculation in which they resimulated the inner regions of a halo with a live DM halo of similar resolution to that of the gas after the formation of an initial sink particle. The effects of DMA were not, however, included.…”
Section: Accuracy Of Dm Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of the latter lack the right resolution to resolve the DM cusp inside it, and actually "switch off" DM after (or sometimes even before) the formation of a hydrostatic object, as a consequence of the fact that the gravitation potential become totally dominated by the baryons in a standard scenario. A recent study, [10], has explored the sub-resolution domain including a hyperrefined DM particle population, originally set with a cusp distribution. It was found that the original DM cusp got modified by the formation of the fragments, and that there is a displacement between the center of the DM cusp (whose profile remains radial in good approximation) and the position of the most massive hydrostatic object.…”
Section: Caveatsmentioning
confidence: 99%